Imunização da criança com transtorno do espectro autista: material educativo para equipe de enfermagem - Araujo, Aurora Tontini de (2024)
Autism is a disorder that can affect several aspects of development, such as the social, cognitive, and language areas, weakening the individual’s communication and causing several impairments. To ensure that children with this condition receive adequate care to promote health and prevent injuries, it is important that nursing professionals strengthen their care practices. This is to serve them in a competent and humane way, respecting their singularities. Therefore, this work aimed to develop educational material to strengthen assistance practices in the immunization process of autistic children. The methodological development occurred in two stages: 1) Requirements elicitation and analysis of interviews with the thirty-six nursing professionals who work in vaccination rooms in Basic Health Units in the city of Foz do Iguaçu/Paraná, in the first half of 2023. This was done to identify the main challenges and strategies to immunize this clientele, with data analyzed from the Collective Subject Discourse; 2) Development of educational technology: construction of the booklet containing scientific evidence, through texts, figures, images, among other resources, on the proposed topic and compiled from information present in the interviews from April to October 2023. The interviewees were nursing professionals, the majority of whom are female, over 40 years of age, and have worked in Primary Care for up to five years. Regarding the Collective Subject Discourse, two discourses emerged - syntheses according to the care processes: Insufficient professional training and continuing education on autismo; Immunization process and inclusion in the health systm, are associated with the lack of adherence to programs aimed at professional training. This is especially true regarding the influence of technological resources to promote the health of autistic children, especially at the time of immunization in health services. The educational technology developed has subtopics: what is autism, warning signs of autism, support levels, autism developmental milestones, visual clues to assist in the process of immunizing autistic people at the basic health unit. The aim is to contribute to demystification in inclusive care and promote the development of assistance strategies for autistic people in healthcare environments. This promotes levels of intellectual, language, and behavioral impairment, the expected developments for each age group, and possible warning signs for the spectrum. Additionally, it encourages the use of visual resources, preparing and adapting the individual’s routine for possible changes in favor of health promotion and immunization. It appears that the use of educational technologies to encourage the dissemination of knowledge about autism, associated with the presence of trained nursing professionals, strengthens care practices and promotes greater adherence to immunization programs. This provides opportunities for in-depth scientific and practical technical development, as well as the development and implementation of technological resources to promote vaccination health.